2020
DOI: 10.1177/0264619620967697
|View full text |Cite
|
Sign up to set email alerts
|

Rapid weight loss in visually impaired judo athletes: Prevalence, magnitude, and methods

Abstract: The aim of this study was to determine the prevalence, magnitude, and methods of rapid weight loss (RWL) in visually impaired (VI) judo athletes, and compare these aspects between males and females. Thirty VI judo athletes (20 men and 10 women) completed a validated questionnaire to assess information about the magnitude and methods of RWL. Simple frequency was used to describe the influence and methods in all athletes and according to sex. Moreover, the t test was used to compare the variables between the sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 19 publications
(47 reference statements)
0
10
2
Order By: Relevance
“…Coaches were the most influential people to all athletes, regardless of gender, while parents and physicians were the least influential. This deviates to some extent from previous studies, especially in terms of parental influence ( Kons et al, 2020 ; Drid et al, 2021 ; Figlioli et al, 2021 ; Todorovic et al, 2021 ). It is possible that the athletes in our study were older, and therefore there were not influenced by their parents.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Coaches were the most influential people to all athletes, regardless of gender, while parents and physicians were the least influential. This deviates to some extent from previous studies, especially in terms of parental influence ( Kons et al, 2020 ; Drid et al, 2021 ; Figlioli et al, 2021 ; Todorovic et al, 2021 ). It is possible that the athletes in our study were older, and therefore there were not influenced by their parents.…”
Section: Discussioncontrasting
confidence: 99%
“…Athletes in our sample started their RWL practices as adults (19 years old). These results, however, are different from results obtained in previous studies (Berkovich et al, 2016;Kons et al, 2020;Drid et al, 2021;Figlioli et al, 2021;Todorovic et al, 2021), while some reports indicate that athletes even as young as 5 years old lost weight to compete (Sansone and Sawyer, 2005). A possible explanation may be in the fact that our respondents started to train grappling in later years, compared to athletes from the mentioned studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In addition, these athletes can effectively improve lower and upper limb power if they train at the optimum power zone 34 . Concerning nutritional strategies for competition, a survey among male and female Brazilian para-judokas found that most lost weight to compete, predominantly through gradual dieting and increased exercise volume 35 …”
Section: Resultsmentioning
confidence: 99%
“…34 Concerning nutritional strategies for competition, a survey among male and female Brazilian para-judokas found that most lost weight to compete, predominantly through gradual dieting and increased exercise volume. 35 Two studies carried out clinical evaluations and found signs of athlete's heart in Brazilian para-judokas, 36,37 identifying the presence of mild cardiac adaptations to training in the Paralympic judo team. 37 In closing, one study tested the psychometric suitability of an adapted Special Judo Fitness Test for para-judokas through two separate adaptations involving sonorous or tactile stimuli.…”
Section: Physical Fitnessmentioning
confidence: 99%